Springshed: identifying recharge areas of drying springs and lakes with water quality in Southwestern Bhutan. / (Acc. :D2764) - Jambay; Tarayana Foundation (Thimphu : Taranaya Foundation, 2022)
Bhutan has experienced a growing water shortage during the past decade as nearby springs, streams, lakes and other water sources have dried up. Climate impact assessments indicated that temperatures in Bhutan will rise, especially in the north. This will lead to a change in precipitation patterns, which will contribute to the drying out of water sources. During a recent field visit to assess water sources, villagers wanted us to save their water sources by providing funds to fence the water sources off. We tried to tell them that merely protecting the spring would not safeguard water sources from drying in the future. It does not address the problem of where water is entering the ground and how that area is being protected. The first step toward a solution is to clear up this lack of understanding of groundwater. In the past, the assumption was that water source protection meant physically fencing off or protecting the point where springs discharged. While it is crucial to keep the water collection point clean and free from pathogens, that is not where the problem of water quantity is best addressed. The purpose of this book is to go beyond what has been done to protect water sources and explore the potential recharge zones of drying lakes and springs based on the best science available at the time. This book on the mapping of recharge areas is ground-breaking and will help our water managers in Bhutan target investments in the right place for the best return on their investment. We have translated the results into plain language with images to assist policymakers who plan development activities. This also addresses water quality and potential changes to water balance, through changes in evapotranspiration, and in this way, we have developed science-based water source management concepts for our region. It is our hope that the book will be useful to our nation!
Includes bibliographies.
Keywords: 1. Springshed-- Southeastern Bhutan. 2. Springs and lakes-- Bhutan. 3. Water quality--Bhutan